Enzymuria-Early Predictors of Acute Kidney Injury in Animals - Sanap, M. J.; Yeotikar, P.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Enzymuria is recently being used as valuable tool for the diagnosis of acute kidney injury (AKI), and urinalysis in clinical cases.  The origin of enzymes from different parts of the kidney has diagnostic importance. Enzymes of kidney origin, namely those from brush border of proximal tubuli  were recognized for their clinical significance inanimals. Now a days, enzymes are more specifically used as tubular markers which determine the location and severity of kidney damage. These enzymes are glutathione S-transferase (GST), N-acetyl-β-D-glucosaminidase (NAG), β-galactosidase (β-GAL), γ-glutamyltranspeptidase and alkaline phosphatase are used as early diagnostic markers of kidney injury. Normally, enzymes originates from serum (as glomerular filtrate), renal tubular cells, and the urogenital tract (epithelial cells, glandular secretion, and semen). The contribution of serum enzymes is negligible for most urinary enzymes because they are relatively larger (> 80 kDa), due to which those marker enzymes do not sieve through the glomerular membrane and appear in the urine. Urinary enzymes have also been used to determine the presence and location of renal tubular injury. Some bacterial or viral infections can damage kidney tubules, which result in the leakage of some enzymes from the tubular epithelium. Various nephrotoxic drugs used in clinical therapeutics, along with some contrast media may lead to acute kidney injury. Enzymes of kidney origin may be released due to damage to the brush border epithelium.  Especially, NAG- a lysosomal enzyme in renal tubular epithelium released into urine in response to tubular damage. These enzymes could be increased or identified in urine of urinary tract infected animals.
Keywords: Acute Kidney Injury; Diagnostic Markers; Enzymuria; Nephrotoxic Drugs; and Urinary Enzymes